Pemberdayaan Masyarakat melalui Pembuatan Konten Edukasi Fisioterapi Wellness Berbasis Canva dan Youtube untuk Mendorong Gaya Hidup Aktif dan Sehat di Kelurahan Malabar - Halomoan, Roni; Rahman, Ika; Gunawan, Ramdhan; P Lifianto, Panji; Insani, Siti; Rosita, Rosita; Amanda, Fadila (LPPM Politeknik Piksi Ganesha, 2024)
This community service activity aims to increase awareness and participation of the Malabar Village community in implementing an active and healthy lifestyle through the creation and publication of Canva and YouTube-based educational content on wellness physiotherapy. The program was carried out by a team of physiotherapy lecturers and students over a period of two months, using a participatory learning and digital content empowerment approach. The activity methods included training in educational content creation, storyboard development, filming educational physiotherapy videos, and publishing them through the community's YouTube channel. A total of 25 participants from the general public and health cadres actively participated in this activity. The results showed an average increase in knowledge about physical activity and fitness of 30%, as well as an increase in digital content creation skills of 75%. In addition, the community showed high enthusiasm in managing social media for health education. This program proves that the combination of wellness physiotherapy and digital literacy can be an effective strategy for building an active lifestyle culture at the community level.